A NEW ADHESIVE COMPOSITION FOR THE MANUFACTURE OF CORRUGATED CARDBOARD - ESHBAEVA, ULBOSIN; NISHANOV, AKBARJON; ZUFAROVA, DILOBAR (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article is devoted to the complete coverage of information about the composition of a new glue with bactericidal properties used in the manufacture of corrugated cardboard products. The main goal of this article is to form the main technological parameters in forming the structure of the corrugated cardboard product, connecting the layers to each other.